Fulfillment Right Child on Education and Welfare Reviewed From Islamic Family Law Perspective - Dila Shinta; Amru Syahputra Lubis (SEAN Institute, 2025)
This research discusses the fulfillment of children's rights to education and welfare from the perspective of Islamic family law and compares it with Indonesian positive law. In Islam, children are seen as trusts who have fundamental rights such as education, welfare and protection. Meanwhile, national law has ratified the Convention on the Rights of the Child through Presidential Decree no. 36 of 1990 and regulates it further in Law no. 35 of 2014. However, implementation in the field still faces various structural and cultural obstacles. This research uses a normative-sociological approach with a literature study method. The research results show that although normatively there are similarities between Islamic law and positive law, the fulfillment of children's rights has not been implemented optimally. Therefore, synergy is needed between family, community and state to ensure the fulfillment of children's rights as a whole .